2017
DOI: 10.1371/journal.pone.0168625
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Liquid Based Cytology and Ancillary Techniques in the Peritoneal Washing Analysis: Our Institutional Experience

Abstract: BackgroundThe cytological analysis of peritoneal effusions serves as a diagnostic and prognostic aid for either primary or metastatic diseases. Among the different cytological preparations, liquid based cytology (LBC) represents a feasible and reliable method ensuring also the application of ancillary techniques (i.e immunocytochemistry-ICC and molecular testing).MethodsWe recorded 10348 LBC peritoneal effusions between January 2000 and December 2014. They were classified as non-diagnostic (ND), negative for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
2
14
1
Order By: Relevance
“…Seventy‐one studies were designed as a cohort, and nine were case‐control studies . Thirty‐three studies explicitly mentioned that the subjects were recruited consecutively …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy‐one studies were designed as a cohort, and nine were case‐control studies . Thirty‐three studies explicitly mentioned that the subjects were recruited consecutively …”
Section: Resultsmentioning
confidence: 99%
“…In two studies, touch smears were assessed, and in the rest of the studies, the smears and/or cell blocks were prepared from the sediments after centrifuging the serous fluid samples. The cytologic evaluation was performed on only smears in 43 and on both smears and cell blocks in 10 studies . In another 10 studies, cell blocks were prepared in addition to smears when the amount of serous fluid was sufficient …”
Section: Resultsmentioning
confidence: 99%
“…After scraping off of all cytological material within an encircled spot, our single-shot MS analysis achieved identification of a total of 4,839 proteins in a relatively short time without fractionation, which is a comparable depth of proteome coverage to that reported in a previous study (29). Carvalho et al performed LC-MS of conventional bronchial cytology pellets obtained by centrifugation, unlike our harvesting of cellular material from one liquid-based cytology slide from each patient, which can maximize the application of ancillary tests, as well as preserve residual samples for the preparation of additional slides for further molecular analysis, unlike pellet-based testing (30). The harvest of cells directly from cytology slides is still challenging because of the unique characteristics of sample fixation and the limited number of cells from each cytology slide as opposed to FFPE-or FACs-based sorted samples, which are replicable for preparation in proteomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…17 Other institutions have also highlighted improvements in the sensitivity and specificity of peritoneal washings from using a wide range of markers. 40 Recent reports have indicated that the detection of carcinoembryonic antigen messenger RNA by reverse transcriptionpolymerase chain reaction is useful for evaluating subclinical tumor cell dissemination in peritoneal lavage fluid. 41 Also, additional gene mutational assays may corroborate the role of cytology to confirm malignancy but also to add prognostic parameters to the patient outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Our center has investigated molecular testing when cytology material is the only specimen source available and reporting high efficiency using cytology specimens for molecular testing to detect EGFR or KRAS mutation in patients with lung cancer . Other institutions have also highlighted improvements in the sensitivity and specificity of peritoneal washings from using a wide range of markers . Recent reports have indicated that the detection of carcinoembryonic antigen messenger RNA by reverse transcription‐polymerase chain reaction is useful for evaluating subclinical tumor cell dissemination in peritoneal lavage fluid .…”
Section: Discussionmentioning
confidence: 99%